Optimization of ferroelectric tunnel junction TFET in presence of temperature and its RF analysis. (October 2019) - Puja, Ghosh; Goswami, Rupam; Bhowmick, Brinda
Abstract: This paper proposes a device incorporating ferroelectric tunnel junction which analyzes the concept of tunneling across a silicon doped hafnium oxide ferroelectric. Variation of electrical parameters with ferroelectric thickness has been examined. Subthreshold swing (SS) of 40 mV/dec has been achieved with ferroelectric thickness of 2 nm. An increasing trend in the ION /IOFF ratio is observed with the increase in ferroelectric thickness. Moreover, the impact of temperature (300 K–500 K) on drain current as well as various RF parameter performance such as gate capacitance (CGG ), transconductance (gm), output conductance (gd ), intrinsic delay, intrinsic gain (gm /gd ), cut off frequency (ft ) and transconductance frequency product (TFP) has been studied.